cos(π/2+α)=-sinα转换过程
1个回答
利用两角和的余弦公式
cos(π/2+α)
=cosπ/2·cosα-sinπ/2·sinα
=0-1×sinα
=-sinα
相关问题
sin(π/2+α)·cos(π/2-α)/cos(π+α)+sin(π-α)·cos(π/2+α)/sin(π+α)=
已知tanα=√2/2,cos2(π-α)+sin(π+α)cos(π-α)+2sin2(α-π)要详细过程~
化简[sin(π/2+α)*cos(π/2-α)]/cos(π+α)+[sin(π-α)*cos(π/2+α)]/sin
化简[sin(π/2-α)cos(π/2-α)]/cos(π+α)-[sin(π-α)cos(π/2-α)]/sin(π
设f(α)=[2sin(π+α)cos(π-α)-cos(π+α)]/[(1+sin^2α+sin(π-α)-cos^2
设f(α)=[2sin(π+α)cos(π-α)-cos(π+α)]/[(1+sin^2α+sin(π-α)-cos^2
..sin^2(π+α)*cos(π+α)*cos(-α-2π)/tan(π+α)*sin^3(π/2+α)*sin(-
若sin(α-π)=2cos(2π-α),求[sin(π-α)+5cos(2π-α)]/[3cos(π-α)-sin(-
求值【sin(2π-α)sin(π+α)cos(-π-α)】/【sin(3π-α)-cos(π-α)】
已知f(α)=sin(π−α)cos(2π−α)cos(−α+32π)cos(π2−α)sin(−π−α)